Impact of dementia: Health disparities, population trends, care interventions, and economic costs. Issue 7 (10th July 2021) - Aranda, María P.; Kremer, Ian N.; Hinton, Ladson; Zissimopoulos, Julie; Whitmer, Rachel A.; Hummel, Cynthia Huling; Trejo, Laura; Fabius, Chanee
Abstract: Introduction: The dementia experience is not a monolithic phenomenon—and while core elements of dementia are considered universal—people living with dementia experience the disorder differently. Understanding the patterning of Alzheimer's disease and related dementias (ADRD) in the population with regards to incidence, risk factors, impacts on dementia care, and economic costs associated with ADRD can provide clues to target risk and protective factors for all populations as well as addressing health disparities. Methods: We discuss information presented at the 2020 National Research Summit on Care, Services, and Supports for Persons with Dementia and Their Caregivers, Theme 1: Impact of Dementia . In this article, we describe select population trends, care interventions, and economic impacts, health disparities and implications for future research from the perspective of our diverse panel comprised of academic stakeholders, and persons living with dementia, and care partners. Results: Dementia incidence is decreasing yet the advances in population health are uneven. Studies examining the educational, geographic and race/ethnic distribution of ADRD have identified clear disparities. Disparities in health and healthcare may be amplified by significant gaps in the evidence base for pharmacological and non‐pharmacological interventions. The economic costs for persons living with dementia and the value of family care partners' time are high, and may persist into future generations. Conclusions: Significant research gaps remain. Ensuring that ADRD healthcare services and long‐term care services and supports are accessible, affordable, and effective for all segments of our population is essential for health equity. Policy‐level interventions are in short supply to redress broad unmet needs and systemic sources of disparities. Whole of society challenges demand research producing whole of society solutions. The urgency, complexity, and scale merit a "whole of government" approach involving collaboration across numerous federal agencies.